Pengaruh Ukuran Perusahaan, Likuiditas dan Profitabilitas Terhadap Pengungkapan CSR Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2018-2021 - Almaidah Khoiriah; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2023)
CSR disclosure is an important aspect in the company's sustainability. It’s because companies that are profitable in the long term are companies that operate on the principle of sustainability. The company's decisions are not only based on the profit motive, but also consider the impact on the community around the company. The purpose of this study is to determine the effect of firm size, liquidity, profitability on CSR disclosure. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. The purposive sampling technique is used by the writer for this research. The method of data analysis is using descriptive statistical analysis, normality test, classical assumption test, multiple regression analysis and hypothesis testing. The results showed that firm size had a negative but not significant effect, then liquidity had a positive and significant effect, while profitability had a positive but not significant effect.Keywords : Company size, liquidity, profitability and CSR